IoT-based LPG Leakage Detector System with Safety Alert Mechanism - Ahmad Shamsudin, Asma Afifah; Baharudin, Elfarizanis (Evolution in Electrical and Electronic Engineering, 2021)
The Internet of Things (IoT) is a growing network of physical devices that are connected to various kinds of sensors and are capable of exchanging data with the presence of an internet connection. One of the systems that using IoT is a gas leakage detector. This study aims to design a liquefied petroleum gas (LPG) leakage detector system with the aid of IoT and safety alert mechanism. The main issue of gas leakage is people do not realize when it happens, therefore the method and purpose of this paper to build a gas leak detector device with IoT apply and with several ways to notify user the presence of a gas leak. The circuit of the LPG leakage detector system is created using Proteus software. The IoT Platform use in this project is Blynk mobile application for user to easily connect and monitor the device by using smartphones. The theory of the circuit is based on the gas sensor to measure the gas leakage in percentage and parts per million (ppm). Besides, for the testing conditions, the gas leakage detector device is tested in two situations, first at open surroundings with different distances between the device and the source of gas, and second test in a different volume of the box. In a conclusion, the gas leakage detector system works as intended, the results show that the system would alert the user when the gas leakage is detected. User will receive a text message, email, and alarm that connected to the device once the system detects the presence of gas leakage.